Federico Incardona and Giovanni Damiani - Carapezza, Paolo Emilio (Interdisciplinary Studies in Musicology, 2018)
Together with Sciarrino and Casale, Incardona and Damiani are the most important composers trained at Palermo University’s Musicological Institute. Federico Incardona (Palermo, 1958-2006) reconciles the social commitment of Berg and the political tension of Nono with the sublimated eroticism of Szymanowski. If Nono’s works, like those of Evangelisti in a different way, blend dodecaphonic dialectic with the corporeity of the sound of Varèse, Incardona blends Evangelisti’s sonorous cosmogony with the erotic immediateness of Bussotti. But his principal reference point is Mahler. His music is rich in meaning and strong emotional intensity, concentrated and sublimated: it is like “processes of denuding of the melody, carnal embraces between the parts, dodecaphonic series modelled on the body of the loved one” (Spagnolo). Its “new linearity and temporal tension”, is wedded to the “absolute primacy of expression and emotion”, in full awareness of the “deep unity of emotion and knowledge” (Lombardi Vallauri). Indeed, in the intense expressionism of his music, dodecaphonic construction is always at the service of a dialectical discourse which is dense and deep, but - in his last works - clear and fluid like a melody by Bellini. “Infinite melos”, Marc Crescimanno defines it: harmonic richness and dense hétérophonie complexities are blended; the counterpoint is based “on the superimposition of manifold variations on the same figure, with precise control of the vertical encounters on its melodic-harmonic hinges”. Born into a dynasty of engineers and architects, Giovanni Damiani (Palermo, 1966) is himself an engineer and architect, but in sound space. Rather than music, his works are organized Sound: “embodiment of the intelligence inherent in sounds themselves”, in the manner of Varèse, and specifically “sound vegetation”, in the manner of Bartok. His most important work, Salve follie precise (1998-2004: on a libretto in verse by Francesco Carapezza, based on Semmelweis et l’infection puerpérale that Louis-Ferdinand Céline wrote between 1924 and 1929), represents precisely the germination of life (of algae from water, of grass from rock, of man from woman, of sounds from Sound) and the threats of death that surround it, that is to say of regression of the animal and vegetable kingdoms to the mineral kingdom. In it Damiani exclusively uses, as previously in the great symphony Matrice/Organon (1995), natural harmonic sounds. We thus assist at harmonic germination; Sound generates sounds, the Note generates notes. If Damiani as a musicologist follows on from Réti, as a composer he follows on from Schenker. For him the note, seen as pure Sound internally structured a priori, is everything: the universe of artistic creation in sound space is only unfolding of the tension internal to the note itself. Everything (melody, tonality, polyphony, harmony), as Cesare Brandi wrote, “comes from the very nature of the note, which is, in the stratification of harmonics, tonic, isolated note (of a melody), vertical chord and horizontal encounter of polyphonic lines”.